Avoiding the middle-income trap: Korean lessons for China? - Michael Murach; Helmut Wagner; Jungsuk Kim; Donghyun Park (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2018)
We analyze and compare the pattern of economic growth and development of China and South Korea in the postwar period. Geographical proximity and cultural affinity between the two countries, as well as the key role of the developmental state in the economies of both countries, suggests that an analytical comparison would be a meaningful and valuable exercise. Furthermore, Korea is one of the few economies that jumped from middle income to high income in a short period, and thus offers potentially valuable lessons for China. The Asian giant moved from low income to middle income very quickly but now faces the challenge of graduating to high income. In this paper, we empirically assess the main drivers of economic growth in China and Korea, and then identify the time period when Korea was at a similar state of structural change as today's China. In addition, we examine the trend and pattern of Korea's economic growth from that point on. We will analyze and compare key reforms that promoted growth in the two countries. Lastly, we sift through our empirical evidence to assess the prospects for China to follow Korea's footsteps in transitioning from middle income to high income relatively quickly.
urn:nbn:de:hbz:708-dh9404
Keywords: O57; O47; O53; 330; China; Korea; middle-income trap; economic growth; economic development; growth policy; development policy